Value Creation dengan Penerapan Prinsip-Prinsip Lean Manufacturing dalam Accounting - Rina Nopianti; Andreas Tri Panudju; Umi Marfuah (Owner : Riset dan Jurnal Akuntansi, 2019)
In many cases, some conventional accounting practices are no longer compatible with the complex manufacturing environment. The proposed this research is to inspire a systems thinking theory and a value chain management, building a business model that prioritizes customers. The objective of this paper is to find out how accounting techniques can optimize of resource utilization wihich would lead in creating value. The second objective is to minimize the lack of conventional accounting using the accounting method that appears. The method in this shis paper is a qualitative research by considering the inductive method designed as a single case study. Empirical data is used based on classic single case control studies that embedded designs including survey data, academic papers theoretical reviews, data collection from interviews, annual reports and documents collected from case companies. The research found that the management accounting system could be integrated in the framework of Just in Time (JIT) + Total Cost (TC) + Time Driven- Activity Based Costing (TD-ABC) + Balance Scorecard (BSC) to develop lean accounting. The utilization of resource is optimized after non-value added activities are eliminated.